Lethal concentration of clomazone, metsulfuron-metil, and quinclorac for silver catfish, Rhamdia quelen, fingerlings - Miron,Denise dos Santos (2004)
The goal of the present work was to determine the lethal concentration (LC50) (96h) of clomazone, metsulfuron-methyl, and quinclorac, herbicides used in rice culture, for the silver catfish, Rhamdia quelen. Fingerlings were exposed to different concentrations of the herbicides. The LC50s were 7.32µL L-1 for clomazone and 395mg L-1 for quinclorac. The LC50 for metsulfuron-methyl was not obtained since all fingerlings survived even at 1200mgL-1. Probably only clomazone can lead to mortality among silver catfish reared in the rice culture system.